HOSPITAL IMAGE DYNAMICS IN SERVICE RECOVERY: MODERATION OF EMOTIONAL INTELLIGENCE: Received: 25th January 2024 Revised: 03rd April 2024, 04th April 2024 Accepted: 25th January 2024 - Thanuset Chokpiriyawat; Kampanat Siriyota (LIFE: International Journal of Health and Life-Sciences, 2024)
This conceptual paper contributes to the academic literature by elucidating the interplay between brand image dimensions, service recovery strategies, customer satisfaction, and word-of-mouth communication and revisiting intentions in the context of private hospitals in Thailand. The findings of this study provide a foundation for future research endeavors by offering insights into the potential moderating role of emotional intelligence in shaping service recovery outcomes. Moreover, the alignment of our results with theoretical frameworks such as Expectancy-Confirmation Theory (ECT) and Social Exchange Theory (SET) suggests avenues for exploring similar phenomena in different industries. Practically, our findings offer actionable implications for private hospitals to enhance customer retention by strategically managing brand image dimensions and incorporating emotional intelligence considerations into service recovery efforts. Future research could delve deeper into the nuanced dynamics of these relationships across diverse cultural and organizational contexts, thereby enriching our understanding and offering practical guidelines for service-oriented businesses globally."